2020
DOI: 10.1136/bmjdrc-2019-000982
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of mouse models of diabetes-associated ulcers

Abstract: Mouse models are frequently used to study diabetes-associated ulcers, however, whether these models accurately simulate impaired wound healing has not been thoroughly investigated. This systematic review aimed to determine whether wound healing is impaired in mouse models of diabetes and assess the quality of the past research. A systematic literature search was performed of publicly available databases to identify original articles examining wound healing in mouse models of diabetes. A meta-analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Hair follicle stem cells have been shown to play an indispensable role in wound healing as skin areas with denser hair tend to heal faster (Martinot et al, 1994;Zomer & Trentin, 2018). Because of these reasons, the reliability of the animal diabetic wound models has been questioned over decades due to the low translational relevance into clinical wound healing scenarios (Gordillo et al, 2013;Huynh et al, 2020).…”
Section: Experimental Model For Diabetic Foot Ulcermentioning
confidence: 99%
See 1 more Smart Citation
“…Hair follicle stem cells have been shown to play an indispensable role in wound healing as skin areas with denser hair tend to heal faster (Martinot et al, 1994;Zomer & Trentin, 2018). Because of these reasons, the reliability of the animal diabetic wound models has been questioned over decades due to the low translational relevance into clinical wound healing scenarios (Gordillo et al, 2013;Huynh et al, 2020).…”
Section: Experimental Model For Diabetic Foot Ulcermentioning
confidence: 99%
“…Hence, this highlights the need for alternate experimental models that match the 3Rs (refinement, reduction, and replacement) approaches while improving the translational relevance (Díaz et al, 2020). Reviews regarding the use of diabetic animals in DFU research have been published elsewhere (Gao et al, 2017;Huynh et al, 2020;King, 2012;Sriram et al, 2018;Velander et al, 2008), hence it will not be covered in this review. Apart from animal models, human skin biopsies have also been employed as ex vivo models for therapeutic screening (Abd et al, 2016;Franz et al, 2009;Sidgwick et al, 2016), albeit their limited availability and inter-individual variations often restrain them from being widely established (Dumont et al, 2015).…”
Section: Experimental Model For Diabetic Foot Ulcermentioning
confidence: 99%
“…This is supported by a recent systematic review that suggested the need for refinement of currently used mouse models of diabetes-associated ulcers in order to make them more clinically relevant. 25 Five different interventions were tested in the included studies and reported to successfully improve healing rate through mechanisms such as promoting angiogenesis, collagen deposition, re-epithelialization and increased expression levels of proliferative markers such as VEGF and increased anti-inflammatory cytokines such as interleukin-8 in addition to reduction of leukocyte infiltration and reduced expression levels of inflammatory cytokines such as TNF 15 16 18-20 (table 3). The risk of bias and reporting quality of three of these studies was considered high but none of the models used were considered to be highly clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent systematic review that suggested the need for refinement of currently used mouse models of diabetes-associated ulcers in order to make them more clinically relevant. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In mice and rats, the skin is thin and fragile, whereas the subcutaneous layer consists of a special muscular striatum, panniculus carnosus (absent in humans), which causes more rapid contraction and facilitates wound healing [120]. Nevertheless, rodents are widely used in experimental models of diabetic wound healing and a number of them provided experience, which allows for further optimization of models in the aspects such as glycemic levels, the method of induction of DM, or duration of DM [121]. The advantages and disadvantages of different animal models used in the studies on diabetic wounds are given in Table 2 A study conducted by the authors of this review showed that the duration of hyperglycemia in rats might reflect the long-term uncompensated course of DM in humans [123].…”
Section: Type 2 Diabetesmentioning
confidence: 99%